Taxonomic review of the genus Indomyrlaea Roesler & Küppers 1979 of China, with descriptions of five new species (Lepidoptera: Pyralidae: Phycitinae) - Ren, Yingdang; Yang, Linlin; Li, Houhun (Zootaxa, 2015)
The taxonomy of the Chinese species of the genus Indomyrlaea Roesler & Küppers, 1979 is revised. Five new species, namely I. bannensis Ren & Li sp. nov., I. fastigipalpa Ren & Li sp. nov., I. nigra Ren & Li sp. nov., I. proceripalpa Ren & Li sp. nov., and I. sinuapalpa Ren & Li sp. nov., are described. The following taxonomic changes are proposed: Sandrabatis Ragonot, 1893 and its type species Sandrabatis crassiella Ragonot, 1893 are synonymized with Ceroprepes Zeller, 1867 and Ceroprepes ophthalmicella (Christoph, 1881), respectively; Indomyrlaea phaeella (Hampson, 1903) comb. nov. is transferred from Sandrabatis. The original combination Nephopterix eugraphella Ragonot, 1888 is resurrected from its previous affiliation with Indomyrlaea. A checklist and a key to all the known species of the world are included.